Performance trends and lifecycle savings of implemented solar photovoltaic system in housing development under tropical climat - Dabdoob, Rawia Marwan; Jahn Kassim, Puteri Shireen (International Journal of Advanced Research, 2019)
Along with the green movement in Malaysia, this paper seeks (1) to investigate the performance trends of employed solar photovoltaic system in housing development under tropical climate, (2) to determine the lifecycle savings and payback period of this technology. The research focuses on Mesra Terrace Development which is a Low density housing in Kuala Lumpur, Malaysia as a case study. The research employed a quantitative method for the data collection. The empirical assessment of the after occupancy performance is based on the analysis of energy power as well as savings in both designed and operational phases. The findings indicate that actual energy savings and lifecycle savings have exceeded the estimated values during design phase. Bedsides, the lifecycle saving of the solar photovoltaic system in homes depends so far on the governmental green programs along with the local green industry and market.